Tissue-Derived Stem and Progenitor Cells - Leora J. Tesche; David A. Gerber (Hindawi Limited, 2010)
The characterization and isolation of various stem cell populations, from embryonic through tissue-derived stem cells, have led a rapid growth in the field of stem cell research. These research efforts have often been interrelated as to the markers that identify a select cell population are frequently analyzed to determine their expression in cells of distinct organs/tissues. In this review, we will expand the current state of research involving select tissue-derived stem cell populations including the liver, central nervous system, and cardiac tissues as examples of the success and challenges in this field of research. Lastly, the challenges of clinical therapies will be discussed as it applies to these unique cell populations.